Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter R - Algebra Reference - R.6 Exponents - R.6 Exercises - Page R-25: 23


$\displaystyle \frac{2(m-n)}{mn(m+n^{2})}$

Work Step by Step

$\displaystyle \frac{2n^{-1}-2m^{-1}}{m+n^{2}}$=.........$\displaystyle \frac{1}{a^{n}}=a^{-n}$ ........ $=\displaystyle \frac{\frac{2}{n}-\frac{2}{m}}{m+n^{2}}$ ($\displaystyle \frac{2}{n}-\frac{2}{m}$): comm. denom. =nm $=\displaystyle \frac{\frac{2m}{nm}-\frac{2n}{nm}}{m+n^{2}}$=.........factor out $\displaystyle \frac{2}{nm}$ from the numerator....... =$\displaystyle \frac{2}{nm}\cdot\frac{m-n}{m+n^{2}}$ $=\displaystyle \frac{2(m-n)}{mn(m+n^{2})}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.